A case of Juvenile Systemic Lupus Erythematosus in a pre-pubertal child with atopic eczema - Afzal, Ghazal; Junaid, Shakila; Zahoor, Fatima (Journal of the Pakistan Medical Association, 2024)
Juvenile Systemic Lupus Erythematosus (JSLE) is a subset of SLE, with onset before eighteen years of age and associated with increased mortality and morbidity. JSLE is a complex autoimmune disease with respect to its underlying genetics. It is characterised by the disruption of immune tolerance, resulting in cascade of immune responses including the Th2 response with production of interleukins (ILs) 4,5,10, as seen with allergic disorders. Along with this, polyclonal activation of B lymphocytes results in the production of autoantibodies, particularly of the IgG, IgM and antinuclear IgE autoantibodies. JSLE is frequently recognized in girls. The purpose of this case report is to share an uncommon presentation of JSLE in a 8-year-old boy who was diagnosed as a case of atopic eczema at the age of 8 months and later on, at the age of 4 years, ---Continue